SOSIALISASI : “SANTRI BERTANYA PEMILU MENJAWAB “ BAGI SANTRI DI PONDOK PESANTREN ALKHAIRAAT KOTA GORONTALO - Ramli Mahmud; Sukarman Kamuli; Asmun Wantu (CV. Multi Kreasi Media, 2022)
Involvement active Students in Election Becomes support for existence democracy direct going to Election 2024. As generation successor ambition nation, students have right for get information good Election nor issue political nationality other. In condition certain Students experience constraint in formation and strengthening level cognitive Students as well as preference political Students to Election. over things these, activities devotion this aim give information about Election as a strengthening agenda level cognitive and preferences political Students as well as guide awareness political in apply participation politics. As for what becomes method in implementation activity this covers stages preparation start from observation beginning until provision tools and facilities supporters. In stages implementation use method talk and ask answer. The result of dedication in accordance with project proposals and not there is significant obstacle in its implementation. Support administrator Alkhairaat Gorontalo City and its enthusiasm Students in support activity very effective to achievements destination devotion. Stages evaluation showing that the socialization agenda the has could change attitude students who tend apathetic Becomes active in strengthening level cognitive and preferences political Students to Election. Keywords : Socialization , Santri , Election